2015
DOI: 10.1111/clr.12579
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized controlled clinical study comparing two dental implant types: volumetric soft tissue changes at 1 year of loading

Abstract: OBJECTIVE To evaluate the volumetric changes occurring from prosthesis insertion to the 1-year follow-up (FU) using one-and two-piece dental implants. METHODS Sixty patients were randomly assigned to receive one-piece or two-piece implants. Casts were obtained at baseline (insertion of final reconstruction) and at 1 year of loading. Finally, 33 pairs of casts (BRA = 18, STM = 15) were deemed appropriate for volumetric analysis of the peri-implant tissues. If the patients had more than one implant, one was rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 22 publications
0
73
2
Order By: Relevance
“…Using this simple and noninvasive technique, it was possible to reconstruct precise para-axial images of teeth, including the buccal bone and gingival contour. Compared with other recent studies [1718], this method was associated with a smaller possibility of errors resulting from impression procedures and the use of bulky ultrasonic instruments. In addition, the method described here was also able to measure bone and gingival thicknesses at identical levels and at various depths.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Using this simple and noninvasive technique, it was possible to reconstruct precise para-axial images of teeth, including the buccal bone and gingival contour. Compared with other recent studies [1718], this method was associated with a smaller possibility of errors resulting from impression procedures and the use of bulky ultrasonic instruments. In addition, the method described here was also able to measure bone and gingival thicknesses at identical levels and at various depths.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, digital scanning and assessment methods have been applied to measure the volume of periodontal tissues. This approach has been successfully used to assess volumetric changes in soft and hard tissues in clinical studies [18]. Indeed, studies have demonstrated the precision and reliability of this noninvasive method [19], although the possibility of introducing errors with the impression-model fabrication procedure has also been described.…”
Section: Introductionmentioning
confidence: 99%
“…The superimposed STL files allowed for measuring the changes in tissue contours from BS‐6M, BS‐1Y, and 6M‐1Y using a previously reported methodology . The following measurements were performed: Linear measurements: from the cross‐sectional views at the middle of the crown at BS, a line coinciding with the axis of the tooth was drawn and then, perpendicular lines to this axis were drawn at 1, 2, 3, 4, and 5 below the GM.…”
Section: Methodsmentioning
confidence: 99%
“… Horizontally, the distance between the line coinciding with the axis of the implant and the buccal soft tissue outline was measured at 0,2 4 and 6 mm below the gingival margin (IMI) or alveolar ridge (DLI) at both time points. Differences between the two measurements were calculated by substracting BS and FU (Sanz Martin, Benic, Hammerle, & Thoma, ; Sanz‐Martin, Sailer, Hammerle, & Thoma, ). Vertically, the distance between two lines perpendicular to the axis of the implant assessed the changes in tissue height. The first line was coincident with the gingival margin of the tooth (IMI) or the crest (DLI) at BS and the other line with the gingival margin of the implant at FU. …”
Section: Methodsmentioning
confidence: 99%